Crise estrutural do capital e a impossibilidade do retorno às saídas keynesianas - Lima, Elane da Silva (2020)
This article deals with the inherent (genetic) crises in the capital system and its structural crisis. It shows that Keynesian solutions and proposals have become unfeasible in the current stage of accumulation of this sociometabolism. Other reformist measures that do not reach the vital core of the logic of production / reproduction of this system will also do nothing more than just alleviate and mitigate its perverse, destructive consequences and the social barbarity immanent to its current stage. The overcoming and positive transcendence of the sociometabolism of capital will only occur through a radical transformation in the form of organization / production / reproduction of human sociability, culminating in a new historical-social form where the possibility of human self-determination and a new way is of relationship with Nature and other forms of life on the planet.